Bawk & roll - Sauer, Tammi (Sterling Children's Books, 2012)
"Dancing chickens Marge and Lola have flown the coop to shake, wattle, and roll on tour with superstar singer Elvis Poultry. Will the hens bawk at fame and lay a rotton egg in concert? Or will they rise to the top of the pecking order and give the crowds something to crow about?"--From inside flap of dust cover.